(untitled) (Fiep Bulletin - online, 2020)
Objective to characterize the scientific production on the assessment of the health condition of the hospitalized elderly in situations of violence. Method: This is an integrative literature review. The review covered 06 studies available in databases, having as descriptors: elderly health, hospitalization and violence. We evaluated articles published from 2007 to 2018. Two themes were inserted: clinical-epidemiological profile of the elderly population and hospitalization; self-rated health of the elderly in situations of violence. Results: It was identified that socioeconomic, demographic characteristics, functional capacity, health conditions and nutritional status interfere in the self-rated health of the elderly hospitalized in situations of violence and in the planning of services aimed at this public. Conclusion: health conditions influence the daily life activities of the elderly who were hospitalized in situations of violence. It was observed that the knowledge of sociodemographic and health characteristics favors the implementation of actions aimed at evaluating the health of elderly victims of violence. Research on publications in Brazil related to the health condition of hospitalized elderly victims of violence is of fundamental importance, since the population is rapidly aging, with increased life expectancy and the emergence of chronic diseases and disabilities.